2006
DOI: 10.1111/j.1365-2958.2006.05509.x
|View full text |Cite
|
Sign up to set email alerts
|

The dominating outer membrane protein of the hyperthermophilic Archaeum Ignicoccus hospitalis: a novel pore‐forming complex

Abstract: SummaryThe membrane protein Imp1227 (Ignicoccus outer membrane protein; Imp1227) is the main protein constituent of the unique outer sheath of the hyperthermophilic, chemolithoautotrophic Archaeum Ignicoccus hospitalis. This outer sheath is the so far only known example for an asymmetric bilayer among the Archaea and is named 'outer membrane'. With its molecular mass of only 6.23 kDa, Imp1227 is found to be incorporated into the outer membrane in form of large, stable complexes. When separated by SDS-PAGE, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
55
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 54 publications
2
55
0
2
Order By: Relevance
“…I. hospitalis is an anaerobic, hyperthermophilic coccus growing strictly chemolithoautotrophically by reduction of elemental sulfur with molecular hydrogen as an electron donor (24) and fixation of CO 2 via a novel CO 2 fixation pathway (15). Like cells of the other described Ignicoccus species, I. hospitalis cells exhibit a unique morphology; they lack an S layer and are the only archaea which are surrounded by an outer membrane exhibiting a unique protein and lipid composition (4,16,22,26). N. equitans was identified as the first representative of a novel archaeal kingdom, the Nanoarchaeota (12,13,31).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…I. hospitalis is an anaerobic, hyperthermophilic coccus growing strictly chemolithoautotrophically by reduction of elemental sulfur with molecular hydrogen as an electron donor (24) and fixation of CO 2 via a novel CO 2 fixation pathway (15). Like cells of the other described Ignicoccus species, I. hospitalis cells exhibit a unique morphology; they lack an S layer and are the only archaea which are surrounded by an outer membrane exhibiting a unique protein and lipid composition (4,16,22,26). N. equitans was identified as the first representative of a novel archaeal kingdom, the Nanoarchaeota (12,13,31).…”
mentioning
confidence: 99%
“…Following cultivation in 0.5ϫ SME medium inside the lumen of cellulose capillaries, cells of I. hospitalis with N. equitans were processed by high-pressure freezing, freeze substitution, and embedding in Epon as previously described (4,26,27). Digital electron micrographs of ultrathin sections, contrasted with uranyl acetate and lead citrate, were recorded using a slow-scan charge-coupled device camera (Tietz, Gauting, Germany) mounted on a CM12 transmission electron microscope (FEI Co., Eindhoven, The Netherlands), which was operated at 120,000 eV.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that a pore-forming complex promotes interaction between cells of the species Ignicoccus hospitalis, the smallest archaeal cell known so far, and its symbiont Nanoarcheum equitans (Burghardt et al, 2007). Another report has described the importance of an aquaporin for the formation of ectomycorrhizae, a tight association between tree roots and soil fungi.…”
Section: Discussionmentioning
confidence: 99%
“…They are good examples of proteins that evolved to perform several functions, regulating cell selectivity and requirements without undergoing great architectural rearrangements (Pohorille et al, 2005). They are commonly found in the OM of bacteria (Nikaido, 1992) and in archaea (Koebnik et al, 2000), as well as in organelles of symbiotic origin such as leaf peroxisomes, mitochondria and chloroplasts (Bölter & Soll, 2001;Burghardt et al, 2007;Mannella, 1992;Rachel et al, 2002;Reumann et al, 1996). In eukaryotic organelles, porins allow the passage of a variety of essential intermediates for many cellular functions, implying that they are involved in the integration of subcellular structures into the metabolism of the eukaryotic cell.…”
Section: Discussionmentioning
confidence: 99%